2020
DOI: 10.1371/journal.pone.0227201
|View full text |Cite
|
Sign up to set email alerts
|

Severe thiamine deficiency in eastern Baltic cod (Gadus morhua)

Abstract: The eastern Baltic cod (Gadus morhua) population has been decreasing in the Baltic Sea for at least 30 years. Condition indices of the Baltic cod have decreased, and previous studies have suggested that this might be due to overfishing, predation, lower dissolved oxygen or changes in salinity. However, numerous studies from the Baltic Sea have demonstrated an ongoing thiamine deficiency in several animal classes, both invertebrates and vertebrates. The thiamine status of the eastern Baltic cod was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…A modelling comparison of otolith biomineralization in Barents Sea cod versus North Sea cod showed that the formation of the translucent zones in cod otoliths can be attributed to low food intake concurrent with increased water temperature, and that small variations in feeding and temperature corresponded to low contrast growth zones (Fablet et al ., 2011). In the Baltic Sea, environmental and biological drivers that further exacerbate unclear seasonal zonation in cod otoliths appear to be factors that affect fish condition and metabolic activity, such as environmental stress caused by hypoxia (Casini et al ., 2016; Chabot & Claireaux, 2008), low prey availability (Casini et al ., 2016), parasite infestation (Eero et al ., 2015; Mehrdana et al ., 2014) and thiamine deficiency (Engelhardt et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A modelling comparison of otolith biomineralization in Barents Sea cod versus North Sea cod showed that the formation of the translucent zones in cod otoliths can be attributed to low food intake concurrent with increased water temperature, and that small variations in feeding and temperature corresponded to low contrast growth zones (Fablet et al ., 2011). In the Baltic Sea, environmental and biological drivers that further exacerbate unclear seasonal zonation in cod otoliths appear to be factors that affect fish condition and metabolic activity, such as environmental stress caused by hypoxia (Casini et al ., 2016; Chabot & Claireaux, 2008), low prey availability (Casini et al ., 2016), parasite infestation (Eero et al ., 2015; Mehrdana et al ., 2014) and thiamine deficiency (Engelhardt et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with the decline in stock size, a number of changes have been observed in the EBC stock, which include reduced body condition, maturation at a smaller size, increased parasite infestation and thiamine deficiency (Eero et al., 2015; Engelhardt et al., 2020; Horbowy et al., 2016). Additionally, a decline in relative abundance of larger individuals (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased summer temperatures due to climate warming could be the actual driver (Kahrua et al, 2020). Engelhardt et al (2020) proposed that the declining condition and health status in EBC are due to thiamin deficiency, as the thiamin content declined with fish size in a recent investigation on EBC. However, to avoid circularity, it remains to be shown whether the thiamin content in EBC deviates from a regular pattern, or whether the lower thiamin content could be due to some other perturbation, i.e., rather the effect than the cause of the EBC impaired condition.…”
Section: Figure 9 |mentioning
confidence: 99%
“…Several hypotheses have been put forward connecting the decreased productivity to a reduced feeding rate, which could stem from (a) regionally unbalanced fishing (Eero et al, 2012), (b) densitydependent feeding competition due to selective fishing Hornborg, 2014, 2017), (c) the spread of hypoxic seafloor leading to density-dependent growth and lower condition (Casini et al, 2016), and substantially higher natural mortality (Neuenfeldt et al, 2019), or (d) that spread of hypoxic or low oxygen-saturated water may affect metabolism and thereby reducing the rate of digestion and hence food consumption in EBC Casini, 2018, 2019;Brander, 2020). Other hypotheses instead point at the increase of seal parasites, impairing growth and health status (e.g., Horbowy et al, 2016), or at the occurrence of thiamin deficiency affecting EBC among other Baltic animal populations (Engelhardt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%